Feasibility of Short-Term PrEP Uptake for Men Who Have Sex With Men With Episodic Periods of Increased HIV Risk. (15th August 2020) - Egan, James E.; Ho, Ken; Stall, Ron; Drucker, Moe T.; Tappin, Ryan; Hendrix, Craig W.; Marzinke, Mark A.; Safren, Steven A.; Mimiaga, Matthew J.; Psaros, Christina; Elsesser, Steven; Mayer, Kenneth H.
Abstract : Background: Pre-exposure prophylaxis (PrEP) with emtricitabine/tenofovir disoproxil fumarate is efficacious in reducing HIV acquisition. For some gay, bisexual, and other men who have sex with men (MSM), daily ongoing PrEP may be unsuitable for use as a long-term prevention strategy because of episodic risk, cost issues, or concerns about the biological consequences of medication. Setting: This study evaluated the feasibility of short-term, fixed-interval episodic PrEP (Epi-PrEP) for use among vacationing MSM. We describe the feasibility of implementing a clinic-based Epi-PrEP pilot program for 48 MSM who reported occasional condomless sex and anticipated a defined high-risk time. Methods: This was a nonrandomized naturalistic study of an observational clinical intervention. The primary outcome assessed was adherence, as measured by self-report and plasma tenofovir levels. Results: Of 54 MSM who enrolled in the study, 48 completed the 3-month visit. The majority (93.7%) had tenofovir concentrations consistent with daily use on returning from vacation. Almost 3/4 reported condomless sex during vacation, and about 1/3 reported recreational drug use. During the 3-month follow-up, 1 participant had become HIV-infected because of a lapse in continued access to the PrEP after study. Although adverse events were common, none were serious. More than 70% of participants indicated an interest in daily ongoing PrEP use. Conclusions: Epi-PrEP was well tolerated by at risk MSM in this study, with high levels of medication adherence. Many participants felt the experience of initiating PrEP while on vacation could be a means for transition to long-term PrEP use.